Semi-quantitative model of the gating of KcsA ion channel. 1. Geometry and energetics of the gating - Kharkyanen, V.N.; Yesylevskyy, S.O.; Berezetskaya, N.M.; Boiteux, C.; Ramseyer, Ch. (Вiopolymers and Cell, 2009)
The aim of this series of papers is to develop the semi-quantitative theory of the gating of KcsA channel. For this purpose the available structural and electrophysiological data and the results of molecular dynamics simulations were used in the context of the concept of dynamical self-organization. In the first paper we describe the simplified model of the geometry and energetics of the gating process. This work is the first successful attempt of combining the structure and dynamics of a real protein and the general concept of dynamic self-organization.